Inorganic binder sand hardening process method and application

By using a method of blown vaporized organic curing agent and gas or immersed organic curing agent, the problem of high addition and high energy consumption in the sand hardening process of inorganic binder in the prior art is solved, and the rapid and low energy consumption hardening effect is achieved, and the strength and collapse of the sand core are improved.

CN119566216AActive Publication Date: 2025-03-07SHENYANG UNIVERSITY OF TECHNOLOGY
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202411651895.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-07
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The existing inorganic binder sand hardening technology for casting has problems such as high addition amount, high energy consumption, low production efficiency and the possibility of toxic substances during hardening.

Method used

The method of blow-frying by blowing gases of vaporized organic curing agent, CO2 and compressed air, or immersing organic curing agent for secondary hardening, is used to improve the hardening rate and quality of inorganic binder sand and reduce the amount of binder used.

Benefits of technology

It realizes rapid hardening of inorganic binder sand, reduces energy consumption and the production of toxic substances, improves the strength and collapse of the sand core, and is suitable for 3D printing technology, saving energy and emission reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566216A_ABST
    Figure CN119566216A_ABST
Patent Text Reader

Abstract

The invention provides an inorganic binder sand hardening process method and application, and the inorganic binder sand hardening process method comprises the following steps: hardening molded inorganic binder sand by adopting one of the following modes: mode I, blowing in a vaporized organic curing agent and at least one of CO2 and compressed air to carry out blowing hardening on the molded inorganic binder sand; in the second mode, the formed inorganic binder sand is subjected to primary hardening by blowing CO2 and compressed air, and then the inorganic binder sand is immersed into an organic curing agent to be subjected to secondary hardening; thirdly, the formed inorganic binder sand is immersed in an organic curing agent to be hardened; mode 4, spraying an organic curing agent on the surface of the formed inorganic binder sand for hardening; alternatively, the method comprises the following steps: forming inorganic binder sand from the crude sand, the binder and the organic curing agent in a layer-by-layer 3D printing manner, and hardening at the same time. According to the method, the hardening rate and quality of the inorganic binder sand can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of casting, and in particular to an inorganic binder sand hardening process method and application. Background Art

[0002] Currently, the main casting binders are phenolic resins and furan resins. When hardening, the organic matter is used together with an acid curing agent. During the process of molding and core making and pouring molten metal into the core, it will decompose and produce toxic gases, which will cause physical harm to operators and cause environmental pollution.

[0003] At present, the inorganic binder sand for casting is mainly water glass sand. The water glass binder is an inorganic material, non-toxic and harmless. Water glass sand can be hardened by blowing carbon dioxide, heating (mold heating, heating furnace or microwave heating), carbon dioxide + compressed air composite blowing hardening, organic ester hardening, and has technical characteristics such as non-toxic and environmentally friendly. However, the above water glass sand hardening technology has the following disadvantages:

[0004] Carbon dioxide blowing hardening alone is prone to overblowing, and the amount of water glass added is high (4-8%). The sand core after casting has poor disintegration and old sand is difficult to regenerate. The heating hardening process can greatly reduce the amount of water glass added, which can achieve an addition of 2.0-3.0%, but it requires uninterrupted and constant temperature input, and has high energy consumption. Carbon dioxide + compressed air composite hardening requires blowing compressed air or other inert gases after the carbon dioxide blowing is completed or during the process, which can effectively avoid the phenomenon of carbon dioxide overblowing, but the overall hardening time is long, affecting production efficiency. The organic ester self-hardening water glass sand process is limited by the slow overall hardening speed, poor fluidity of the mold (core) sand, and low efficient core production. Summary of the invention

[0005] The purpose of the present invention is to provide an inorganic binder sand hardening process method, which can greatly improve the hardening rate and quality of the inorganic binder sand, reduce the use of the binder in the inorganic binder sand, and does not use furan resin, phenolic resin and other organic binders. It has the advantages of low gas emission, green environmental protection, high strength, good disintegration, etc. Through the technology involved in the present invention, inorganic core 3D printing technology can also be realized, without the need for high energy consumption processes such as heating and microwave heating, thus saving energy and reducing emissions.

[0006] In order to achieve the above technical objectives, the technical solutions adopted in this application are as follows:

[0007] In a first aspect, the present invention provides a method for hardening inorganic binder sand, the method comprising: hardening the formed inorganic binder sand by one of the following methods:

[0008] Method 1: Blowing and hardening the formed inorganic binder sand by blowing in vaporized organic curing agent and at least one gas selected from CO2 and compressed air;

[0009] Method 2: The formed inorganic binder sand is hardened once by blowing CO2 and compressed air, and then the inorganic binder sand is immersed in an organic curing agent for secondary hardening;

[0010] Method three, immersing the formed inorganic binder sand into an organic curing agent for hardening;

[0011] Method 4: spraying an organic curing agent on the surface of the formed inorganic binder sand to harden it;

[0012] Alternatively, the method comprises: forming inorganic binder sand by 3D printing layer by layer with raw sand, binder, and organic curing agent, and hardening the inorganic binder sand at the same time;

[0013] The organic curing agent is selected from at least one of methanol, ethanol, ethylene glycol, propanol, acetonitrile and acetone.

[0014] Preferably, in the first method, the formed inorganic binder sand is blown with vaporized organic curing agent and at least one gas selected from CO2 and compressed air, and the gas is blown in one of the following ways:

[0015] Method 1: vaporized organic curing agent, CO2, and compressed air are blown in in any order;

[0016] Method 2: vaporized organic curing agent and compressed air are blown in in any order;

[0017] Method 3: vaporized organic curing agent and CO2 are blown in in any order.

[0018] Preferably, in the method 1, the blowing pressure of the vaporized organic curing agent is 0.05MPa~0.5MPa, and the blowing time is 5s~50s; and / or, the CO2 blowing pressure is 0.05MPa~0.5MPa, and the blowing time is 5s~90s; and / or, the compressed air blowing pressure is 0.05MPa~0.5MPa, and the blowing time is 5s~40s.

[0019] Preferably, in the second method, the CO2 blowing pressure is 0.05MPa~0.5MPa, and the blowing time is 5s~90s; and / or, the compressed air blowing pressure is 0.05MPa~0.5MPa, and the blowing time is 5s~40s; and / or, the inorganic binder sand is immersed in an organic curing agent for secondary hardening, and the immersion time is 0.5s~600s.

[0020] Preferably, in the third method, the time for immersing the formed inorganic binder sand in the organic curing agent is 0.5s to 600s.

[0021] Preferably, in the fourth method, an organic curing agent is sprayed on the surface of the formed inorganic binder sand to harden it, and the hardening is sprayed 1 to 10 times.

[0022] Preferably, the raw material composition of the inorganic binder sand includes: raw sand, binder, and hardening accelerator; wherein, the amount of binder added is 2% to 3% of the mass of the raw sand, and the amount of hardening accelerator added is 0 to 50% of the mass of the binder; more preferably, the binder is water glass or modified water glass.

[0023] Preferably, the forming of inorganic binder sand by 3D printing the raw sand, binder and organic curing agent and hardening the inorganic binder sand at the same time is carried out in one of the following ways:

[0024] Method 1), laying raw sand on the 3D printing instrument, then spraying the binder and organic curing agent on the surface of the raw sand in sequence, and 3D scanning and forming; repeating the above process until the 3D printing is completed;

[0025] Method 2), mix the raw sand and the binder, then spread the mixture on the 3D printing instrument, spray the organic curing agent, and 3D scan and shape; repeat the above process until the 3D printing is completed;

[0026] More preferably, the mass ratio of raw sand, binder and organic curing agent is controlled at 100:2-3:0.1-1.0;

[0027] More preferably, the binder is water glass or modified water glass, and the added amount is 2% to 3% of the mass of the original sand.

[0028] Preferably, a hardening accelerator is added to the raw sand, and the amount of the hardening accelerator added is 1 to 50% of the mass of the binder; more preferably, the hardening accelerator is at least one of bauxite, crystalline silica, amorphous silica, fumed silica, silicon powder, microsilica powder, wollastonite powder, and surface-modified silica.

[0029] In a second aspect, the present invention provides a method for repairing and / or hardening the surface of inorganic binder sand, which uses method 4 of the process method described in the first aspect to repair and / or harden the surface of inorganic binder sand.

[0030] The present invention has the following advantages:

[0031] On the one hand, the inorganic binder sand hardening process method of the present invention can solve the current problems of high addition amount, high energy consumption, low production efficiency and the like of inorganic binder sand. The hardening process will not release toxic substances, the hardening speed is fast, the energy consumption is low, the prepared sand core has high strength, no toxic, harmful or irritating substances are produced during the hardening and casting process, the dehydration process is fast, the working environment can be improved, and it is beneficial to environmental protection.

[0032] On the other hand, the inorganic binder sand hardening process method of the present invention can also be used for repairing sand molds and cores, and for preparing inorganic cores through 3D printing technology. The entire process does not involve high-energy consumption processes such as heating, thereby achieving the goal of energy conservation and emission reduction.

[0033] On the third aspect, an inorganic binder sand obtained in the embodiment of the present invention, namely water glass sand, has a high tensile strength in the "8"-shaped sample prepared according to the casting industry standard, especially the sample has excellent instantaneous strength, which can reach up to 1.3MPa or more, and the 24h tensile strength can reach up to 2.0MPa or more. The instant strength can generally reach 0.4MPa or more, and the 24h tensile strength can generally reach 0.7MPa or more.

[0034] In addition, the inorganic binder sand hardening process method of the present invention is applied to the repair and hardening of sand molds and cores, which can increase the surface hardness by more than 6.4%, and keep the 24h tensile strength unchanged or even better sand molds and cores. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a surface structure diagram of the sand core before and after treatment of Example 28 of the present invention.

[0036] Figure 2 This is a physical picture of the existing use of water-based repair mud to repair the sand core surface. DETAILED DESCRIPTION

[0037] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0038] The prepared molding sand in the present invention includes a casting binder and raw sand, and the raw sand is Dalin scrubbing sand. The strength and gas generation of the prepared molding sand are measured in accordance with GB / T 2684-2009 Testing methods for foundry sand and mixtures.

[0039] The modified water glass used in the embodiment of the present invention is specifically modified by the following method: the following substances are added into the reaction container in order according to the mass ratio: water glass: sodium hydroxide: potassium hydroxide: sorbitol: sodium hexametaphosphate: glucoside: polyvinyl alcohol = 100:3:4:5:5:0.5:0.5, and stirred evenly to obtain the product.

[0040] In addition, there are other modified water glass that can be used in this case, such as: adjusting the modulus through sodium hydroxide, potassium hydroxide, lithium hydroxide, citric acid, ammonium chloride, etc., and improving the strength through organic alcohols such as glucose, sorbitol, and xylitol; improving the disintegration through sodium pyrophosphate, sodium hexametaphosphate, sodium dihydrogen phosphate, and aluminum dihydrogen phosphate; improving the viscosity of water glass and the fluidity of mold (core) sand through anionic or cationic surfactants; improving the anti-hygroscopicity through organic polymers such as PVB, EVA, polyvinyl alcohol, starch, polyacrylic acid, and sodium polyacrylate; in addition to the above-mentioned component modifications, the modification effect can also be optimized by changing the temperature, applying an external magnetic field, high temperature and high pressure, etc.

[0041] The surface-modified silica used in the embodiment of the present invention is modified by the following method: weigh the dried silica powder and add it to a high-speed mixer, add a measured amount of oligomeric short-chain alkyl silane KH550 (KH560 and a mixture of KH550 and KH560 can also be used), the amount of KH550 added is 0.5% of the silica powder (the amount added can be controlled between 0.1 and 1.0%), the modification time is 20 minutes, the stirring speed is 1250r / min, and the reaction product is stirred and discharged at a low speed. There are a large number of active hydroxyl groups on the surface of the silica powder, which is highly hydrophilic, making it very easy to form agglomerates or secondary aggregations, which is not conducive to its dispersion in the material, and thus affects the structure and performance of the material. Therefore, it is necessary to surface modify the silica powder to ensure that it can be stored stably and to improve its dispersibility in the product. In addition, there are other modified silicas that can be used in this case, such as: silane coupling agent modification, organic polymer modification, and modification with other alkaline metal hydroxides, oxides, etc. through high-speed ball milling, or low-temperature sintering.

[0042] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described by preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention. In addition, the following examples are only for illustrating the present invention, but not for limiting the present invention.

[0043] Example 1

[0044] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0045] Step 1, heat the organic curing agent ethanol until it is vaporized, and then pass compressed air into the vaporized organic curing agent at 0.1 MPa to remove the ethanol, and then pass the inorganic binder sand core sample to harden it. After blowing for 30 seconds, close the compressed air gas pipeline;

[0046] Step 2, at 0.15 MPa, pass CO2 gas into the inorganic binder sand core sample for 60 seconds, and then close the CO2 gas pipeline;

[0047] Step 3, at 0.2MPa, compressed air is introduced into the inorganic binder sand core sample for 20 seconds. After the blowing is completed, the tensile strength of the sample is tested with a hydraulic testing machine. The instant strength is measured within 60 seconds and the average value of the sample is taken; after the sample is placed indoors for 24 hours, the final strength of the sample is tested. The results are shown in Table 1 (Examples 2-27, Comparative Examples 1-2 are the same).

[0048] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.5, and 4g of crystalline silica for core making, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, using a hammer-type sample making machine to make 5 samples for parallel testing, which are the same as Examples 1 to 27 and Comparative Examples 1 to 2.

[0049] Example 2

[0050] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0051] Step 1, heat the organic curing agent n-propanol until it is vaporized, and then pass compressed air into the vaporized organic curing agent at 0.2 MPa to remove the n-propanol, and then pass the inorganic binder sand core sample to harden it. After blowing for 30 seconds, close the compressed air gas pipeline;

[0052] Step 2, at 0.15 MPa, pass CO2 gas into the inorganic binder sand core sample for 90 seconds, and then close the CO2 gas pipeline;

[0053] Step 3: At 0.2 MPa, compressed air is introduced into the inorganic binder sand core sample for 30 seconds. After the blowing is completed, the tensile strength of the sample is tested with a hydraulic testing machine. The instant strength is measured within 60 seconds and the average value of the sample is taken. After the sample is placed indoors for 24 hours, the final strength of the sample is tested. The results are shown in Table 1.

[0054] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 4g of microsilica powder to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make the sample.

[0055] Example 3

[0056] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0057] Step 1, heat the organic curing agent ethanol until it is vaporized, pass compressed air into the vaporized organic curing agent at 0.15MPa to remove the ethanol, and then pass the inorganic binder sand core sample into it for hardening, blow air for 30s, and then close the compressed air gas pipeline;

[0058] Step 2, at 0.2 MPa, pass CO2 gas into the inorganic binder sand core sample for 60 seconds, and then close the CO2 gas pipeline;

[0059] Step 3: At 0.15 MPa, compressed air is introduced into the inorganic binder sand core sample for 30 seconds. After the blowing is completed, the tensile strength of the sample is tested with a hydraulic testing machine. The instant strength is measured within 60 seconds and the average value of the sample is taken. After the sample is placed indoors for 24 hours, the final strength of the sample is tested. The results are shown in Table 1.

[0060] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 10g of crystalline silica to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make a sample.

[0061] Example 4

[0062] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0063] Step 1, at 0.2 MPa, pass CO2 gas into the inorganic binder sand core sample for 60 seconds, and then close the CO2 gas pipeline;

[0064] Step 2, at 0.15 MPa, pass compressed air into the inorganic binder sand core sample for 50 seconds, and then close the compressed air gas pipeline;

[0065] Step 3, the organic curing agent methanol is heated to vaporize, and compressed air is passed into the vaporized organic curing agent at 0.15MPa to remove the methanol, and then the inorganic binder sand core sample is passed to harden, and the air is blown for 40 seconds. After the blowing is completed, the tensile strength of the sample is tested with a hydraulic testing machine, and the instant strength is measured within 60 seconds and the average value of the sample is taken; after the sample is placed indoors for 24 hours, the final strength of the sample is tested. The results are shown in Table 1.

[0066] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 10g of fumed silica to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make a sample.

[0067] Example 5

[0068] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0069] Step 1, heat the organic curing agent ethanol until it is vaporized, pass compressed air into the vaporized organic curing agent at 0.15MPa to remove the ethanol, and then pass the inorganic binder sand core sample into it for hardening, blow air for 30s, and then close the compressed air gas pipeline;

[0070] Step 2: At 0.2 MPa, pass CO2 gas into the inorganic binder sand core sample for 60 seconds. After the blowing is completed, use a hydraulic testing machine to test the tensile strength of the sample. The instant strength is measured within 60 seconds and the average value of the sample is taken. After the sample is placed indoors for 24 hours, the final strength of the sample is tested. The results are shown in Table 1.

[0071] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 5g of crystalline silica to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make a sample.

[0072] Example 6

[0073] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0074] Step 1, heating the organic curing agent acetonitrile until it is vaporized, passing compressed air into the vaporized organic curing agent at 0.15 MPa to remove the acetonitrile, and then passing the inorganic binder sand core sample into the sample for hardening, and closing the compressed air gas pipeline after blowing for 30 seconds;

[0075] Step 2: At 0.15 MPa, compressed air is introduced into the inorganic binder sand core sample for 30 seconds. After the blowing is completed, the tensile strength of the sample is tested with a hydraulic testing machine. The instant strength is measured within 60 seconds and the average value of the sample is taken. After the sample is placed indoors for 24 hours, the final strength of the sample is tested. The results are shown in Table 1.

[0076] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 10g of crystalline silica to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make a sample.

[0077] Example 7

[0078] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0079] Step 1, heat the organic curing agent acetone until it is vaporized, and then pass compressed air into the vaporized organic curing agent at 0.15 MPa to remove the acetone, and then pass the inorganic binder sand core sample into it for hardening. After blowing for 60 seconds, close the compressed air gas pipeline;

[0080] Step 2: At 0.15 MPa, compressed air is introduced into the inorganic binder sand core sample for 30 seconds. After the blowing is completed, the tensile strength of the sample is tested with a hydraulic testing machine. The instant strength is measured within 60 seconds and the average value of the sample is taken. After the sample is placed indoors for 24 hours, the final strength of the sample is tested. The results are shown in Table 1.

[0081] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 10g of non-crystalline silica to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make a sample.

[0082] Example 8

[0083] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0084] Step 1, at 0.15 MPa, pass compressed air into the inorganic binder sand core sample for 30 seconds, and then close the compressed air gas pipeline;

[0085] Step 2, at 0.2 MPa, pass CO2 gas into the inorganic binder sand core sample for 60 seconds, and then close the CO2 gas pipeline;

[0086] Step 3, heat the organic curing agent ethanol until it is vaporized, and then pass compressed air into the vaporized organic curing agent at 0.15MPa to remove the ethanol, and then pass the inorganic binder sand core sample to harden it, blowing for 30s. After the blowing is completed, use a hydraulic testing machine to test the tensile strength of the sample, and take the average value of the sample by measuring the instant strength within 60s; after placing the sample indoors for 24h, test the final strength of the sample. The results are shown in Table 1.

[0087] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 10g of crystalline silica to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make a sample.

[0088] Example 9

[0089] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0090] Step 1: Heat the organic curing agent ethanol until it is vaporized, and then pass compressed air into the vaporized organic curing agent at 0.15MPa to remove the ethanol, and then pass the inorganic binder sand core sample to harden it, and blow air for 30s.

[0091] Step 2, at 0.15 MPa, pass compressed air into the inorganic binder sand core sample for 30 seconds, and then close the compressed air pipeline;

[0092] Step 3: At 0.2 MPa, pass CO2 gas into the inorganic binder sand core sample for 60 seconds. After the blowing is completed, use a hydraulic testing machine to test the tensile strength of the sample. The instant strength is measured within 60 seconds and the average value of the sample is taken. After the sample is placed indoors for 24 hours, the final strength of the sample is tested. The results are shown in Table 1.

[0093] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 10g of crystalline silica to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make a sample.

[0094] Example 10

[0095] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0096] Step 1, at 0.2 MPa, pass CO2 gas into the inorganic binder sand core sample for 60 seconds, and then close the CO2 gas pipeline;

[0097] Step 2: Heat the organic curing agent ethanol until it is vaporized, and then introduce compressed air into the vaporized organic curing agent at 0.15 MPa to remove the ethanol, and then introduce the inorganic binder sand core sample for hardening, blowing for 30 seconds. After the blowing is completed, use a hydraulic testing machine to test the tensile strength of the sample, and take the average value of the sample within 60 seconds of measuring the instant strength; after placing the sample indoors for 24 hours, test the final strength of the sample. The results are shown in Table 1.

[0098] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 10g of crystalline silica to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make a sample.

[0099] Embodiment 11

[0100] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0101] Step 1, at 0.15 MPa, pass compressed air into the inorganic binder sand core sample for 30 seconds, and then close the compressed air gas pipeline;

[0102] Step 2: Heat the organic curing agent ethanol until it is vaporized, and then introduce compressed air into the vaporized organic curing agent at 0.15 MPa to remove the ethanol, and then introduce the inorganic binder sand core sample for hardening, blowing for 30 seconds. After the blowing is completed, use a hydraulic testing machine to test the tensile strength of the sample, and take the average value of the sample within 60 seconds of measuring the instant strength; after placing the sample indoors for 24 hours, test the final strength of the sample. The results are shown in Table 1.

[0103] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 10g of crystalline silica to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make a sample.

[0104] Example 12

[0105] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0106] Step 1, at 0.2 MPa, pass CO2 gas into the inorganic binder sand core sample for 30 seconds, and then close the CO2 gas pipeline;

[0107] Step 2, at 0.15 MPa, pass compressed air into the inorganic binder sand core sample for 30 seconds, and then close the compressed air pipeline;

[0108] Step 3: After the blowing is completed, the mold is immersed in anhydrous ethanol, an organic curing agent, for 60 seconds. After the immersion is completed, the tensile strength of the sample is tested with a hydraulic testing machine. The instant strength is measured within 60 seconds and the average value of the sample is taken; after the sample is placed indoors for 24 hours, the final strength of the sample is tested. The results are shown in Table 1.

[0109] The preparation process of the inorganic binder sand core sample includes: mixing 1000g of Dalin scrubbing sand, 20g of casting water glass with a modulus of 2.0, and 10g of crystalline silica to make a core, taking an appropriate amount of the mixture and placing it in an "8"-shaped mold, and using a hammer-type sample making machine to make a sample.

[0110] Embodiment 13

[0111] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0112] The inorganic binder sand was immersed in anhydrous methanol of the organic curing agent for 10 seconds. After the immersion, the tensile strength of the sample was tested with a hydraulic testing machine. The instant strength was measured within 60 seconds and the average value of the sample was taken. After the sample was placed indoors for 24 hours, the final strength of the sample was tested. The results are shown in Table 1.

[0113] The preparation process of the inorganic binder sand core sample is the same as that in Example 8.

[0114] Embodiment 14

[0115] This embodiment provides an inorganic binder sand hardening process method, which differs from Embodiment 13 in that the organic curing agent is ethanol and the immersion time is 50 seconds.

[0116] Embodiment 15

[0117] This embodiment provides an inorganic binder sand hardening process method, which differs from Embodiment 14 in that the immersion time is 10 seconds.

[0118] Example 16

[0119] This embodiment provides an inorganic binder sand hardening process method, which differs from Embodiment 14 in that the immersion time is 100 seconds.

[0120] Embodiment 17

[0121] This embodiment provides an inorganic binder sand hardening process method, which differs from Embodiment 13 in that the organic curing agent is ethylene glycol and the immersion time is 90 seconds.

[0122] Embodiment 18

[0123] This embodiment provides an inorganic binder sand hardening process method, which differs from Embodiment 13 in that the organic curing agent is n-propanol and the immersion time is 40 seconds.

[0124] Embodiment 19

[0125] This embodiment provides an inorganic binder sand hardening process method, which differs from Embodiment 13 in that the organic curing agent is isopropyl alcohol and the immersion time is 30 seconds.

[0126] Embodiment 20

[0127] This embodiment provides an inorganic binder sand hardening process method, which differs from Embodiment 13 in that the organic curing agent is acetonitrile and the immersion time is 80 seconds.

[0128] Embodiment 21

[0129] This embodiment provides an inorganic binder sand hardening process method, which differs from Embodiment 13 in that the organic curing agent is acetone and the immersion time is 70 seconds.

[0130] Embodiment 22

[0131] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0132] Spread Dalin scrubbing sand on the 3D printing instrument, then spray the binder and organic curing agent on the surface of the raw sand in turn, and 3D print it into shape; repeat the above process until the 3D printing is completed. Among them, the binder is casting water glass with a modulus of 2.0, and the organic curing agent is anhydrous ethanol. The mass ratio of raw sand, binder, and organic curing agent is 100:2:0.5.

[0133] The tensile strength of the sample was tested with a hydraulic testing machine, and the instant strength was measured within 60 seconds and the average value of the sample was taken; after the sample was placed indoors for 24 hours, the final strength of the sample was tested. The results are shown in Table 1.

[0134] Embodiment 23

[0135] This embodiment provides an inorganic binder sand hardening process method, which differs from Example 22 in that the binder is modified water glass and the organic curing agent is methanol.

[0136] Embodiment 24

[0137] This embodiment provides an inorganic binder sand hardening process method, comprising the following steps:

[0138] Mix Dalin scrubbing sand and binder, then spread the mixture on the 3D printing instrument, spray the organic curing agent, and 3D scan and shape; repeat the above process until the 3D printing is completed. Among them, the binder is casting water glass with a modulus of 2.0, and the organic curing agent is anhydrous n-propanol. The mass ratio of raw sand, binder, and organic curing agent is 100:2:0.5.

[0139] Embodiment 25

[0140] This embodiment provides an inorganic binder sand hardening process method, which differs from Example 24 in that the binder is modified water glass and the organic curing agent is isopropyl alcohol.

[0141] Embodiment 26

[0142] This embodiment provides an inorganic binder sand hardening process method, which differs from Example 22 in that 1% by weight of the hardening accelerator crystalline silica is added to the Dalin scrubbing sand.

[0143] Embodiment 27

[0144] This embodiment provides an inorganic binder sand hardening process method, which differs from Example 23 in that 1% of the weight of the hardening accelerator microsilica powder is added to the Dalin scrubbing sand.

[0145] Existing sand core surface repair mostly uses water-based repair mud, such as Figure 2 As shown, this water-based repair mud needs to use the residual heat during the sand core forming and application process to achieve the drying and forming effect. For cores at room temperature, especially inorganic sand cores with serious hygroscopic tendency, water-based repair mud is not suitable for surface repair, but will increase the probability of casting defects in the repaired parts. Therefore, the embodiment of the present invention further examines the effect of using method 4 to repair and / or harden the surface of inorganic binder sand, as follows:

[0146] Embodiment 28

[0147] This embodiment provides a method for repairing and hardening the surface of inorganic binder sand, targeting the local loose parts of inorganic binder sand with surface defects such as Figure 1 As shown in Figure A, it is possible to see obvious irregular pores and looseness. These local looseness can easily cause casting defects such as sand inclusion, sand sticking, and nodules during casting. The preparation method of inorganic binder sand is the same as that of Example 1, and inorganic binder sand with surface defects is selected therefrom. The local repair process for the loose part is as follows:

[0148] Place the sand core on the workbench, heat the surface temperature of the sand core to 180℃, apply a layer of inorganic sand on the loose parts, spray the organic curing agent methanol for hardening, the single spraying time is 2s, and repeat the spraying 5 times. Use a sand hardness tester to test the surface hardness of the sand core before and after treatment, measure it 5 times in parallel, and take the average value. The surface structure of the sand core after treatment is as follows Figure 1 As shown in Figure B; and, after the sand cores before and after the treatment were placed in the room for 24 hours, the final strength of the sand cores was tested using a hydraulic testing machine. The results are shown in Table 2 (the same as in Examples 29 to 34).

[0149] Embodiment 29

[0150] This embodiment provides a method for surface repair and surface hardening of inorganic binder sand. The source of the inorganic binder sand is the same as that of Example 28. The specific process is different from that of Example 28 in that the surface temperature of the sand core is 120°C, the organic curing agent is ethanol, and the number of spraying times is 10 times.

[0151] Embodiment 30

[0152] This embodiment provides a method for surface repair and surface hardening of inorganic binder sand. The source of the inorganic binder sand is the same as that of Embodiment 28. The specific process is different from that of Embodiment 29 in that the spraying is performed once.

[0153] Embodiment 31

[0154] This embodiment provides a method for surface repair and surface hardening of inorganic binder sand. The source of the inorganic binder sand is the same as that of Embodiment 28. The specific process is different from that of Embodiment 29 in that the surface temperature of the sand core is 180°C and the number of spraying times is 5 times.

[0155] Embodiment 32

[0156] This embodiment provides a method for surface repair and surface hardening of inorganic binder sand. The source of the inorganic binder sand is the same as that of Example 28. The specific process differs from that of Example 28 in that the surface temperature of the sand core is 200°C, the organic curing agent is n-propanol, and the number of spraying times is 8 times.

[0157] Embodiment 33

[0158] This embodiment provides a method for surface repair and surface hardening of inorganic binder sand. The source of the inorganic binder sand is the same as that of Example 28. The specific process is different from that of Example 28 in that the surface temperature of the sand core is 250°C and the organic curing agent is acetone.

[0159] Embodiment 34

[0160] This embodiment provides a method for surface repair and surface hardening of inorganic binder sand. The source of the inorganic binder sand is the same as that of Example 28. The specific process differs from that of Example 28 in that: the surface temperature of the sand core is 120°C, the organic curing agent is a mixture of methanol and ethanol in a volume ratio of 1:1, and the spraying is performed twice.

[0161] Embodiment 35

[0162] This embodiment provides a method for surface repair and surface hardening of inorganic binder sand. The source of the inorganic binder sand is the same as that of Example 28. The specific process differs from that of Example 28 in that the surface temperature of the sand core is 20°C, the organic curing agent is acetonitrile, and the spraying times are 3 times.

[0163] Comparative Example 1

[0164] This comparative example provides a method for hardening sand with an inorganic binder, and the specific operation is as follows:

[0165] At 0.2MPa, CO2 gas was blown into the inorganic binder sand core sample for 60s. After the blowing was completed, the CO2 gas pipeline was closed; then, compressed air was blown into the inorganic binder sand core sample at 0.15MPa pressure for 30s. After the blowing was completed, the sample was demoulded and sampled. The tensile strength of the sample was tested with a hydraulic testing machine. The instant strength was measured within 60s and the average value of the sample was taken; after being placed indoors for 24h, the final strength of the sample was tested. The preparation process of the inorganic binder sand core sample is the same as that of Example 1.

[0166] Comparative Example 2

[0167] This comparative example provides a method for hardening sand with an inorganic binder, and the specific operation is as follows:

[0168] At 0.2MPa, CO2 gas was blown into the inorganic binder sand core sample through the blowing plate for 60s. After the blowing was completed, the sample was demoulded and sampled. The tensile strength of the "8" type sample was tested with a hydraulic testing machine. The instant strength was measured within 60s and the average value of the sample was taken. After being placed indoors for 24h, the final strength of the sample was tested. The preparation process of the inorganic binder sand core sample was the same as that of Example 2.

[0169] Table 1 Test results of inorganic binder sand core samples of Examples 1 to 27 and Comparative Examples 1 to 2 (average of 5 samples)

[0170]

[0171]

[0172] Table 2 Test results of inorganic binder sand core samples of Examples 28 to 34

[0173]

[0174] The data in Table 1 show that the "8"-shaped specimens prepared according to the casting industry standard using the hardening method of Examples 1 to 27 have higher tensile strength, among which the instant strength can generally reach above 0.4 MPa, and can reach above 1.3 MPa at most, and the 24h tensile strength can generally reach above 0.7 MPa, and can reach above 2.0 MPa at most, while the tensile strength of the specimens obtained by the conventional hardening method in Comparative Examples 1 and 2 are both poor.

[0175] The data in Table 2 show that the inorganic binder sand hardening process method of the present invention is applied to the repair and hardening of sand molds and cores. Whether at room temperature or high temperature, the surface hardness can be increased by more than 6.4%, and the actual surface hardness reaches more than 80 degrees. The 24h tensile strength remains unchanged or even better sand mold and core repair products.

[0176] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. Inorganic binder sand hardening process, characterized in that: The method comprises: hardening the formed inorganic binder sand by one of the following methods: Method 1: Blowing and hardening the formed inorganic binder sand by blowing in vaporized organic curing agent and at least one gas selected from CO2 and compressed air; Method 2: The formed inorganic binder sand is hardened once by blowing CO2 and compressed air, and then the inorganic binder sand is immersed in an organic curing agent for secondary hardening; Method three, immersing the formed inorganic binder sand into an organic curing agent for hardening; Method 4: spraying an organic curing agent on the surface of the formed inorganic binder sand to harden it; Alternatively, the method comprises: forming inorganic binder sand by 3D printing layer by layer with raw sand, binder, and organic curing agent, and hardening the inorganic binder sand at the same time; The organic curing agent is selected from at least one of methanol, ethanol, ethylene glycol, propanol, acetonitrile and acetone.

2. The process according to claim 1, characterized in that: In the first method, the formed inorganic binder sand is blown with vaporized organic curing agent and at least one gas selected from CO2 and compressed air, and the gas is blown in one of the following ways: Method 1: vaporized organic curing agent, CO2, and compressed air are blown in in any order; Method 2: vaporized organic curing agent and compressed air are blown in in any order; Method 3: vaporized organic curing agent and CO2 are blown in in any order.

3. The process according to claim 1 or 2, characterized in that: In the method 1, the blowing pressure of the vaporized organic curing agent is 0.05MPa~0.5MPa, and the blowing time is 5s~50s; and / or, the CO2 blowing pressure is 0.05MPa~0.5MPa, and the blowing time is 5s~90s; and / or, the compressed air blowing pressure is 0.05MPa~0.5MPa, and the blowing time is 5s~40s.

4. The process according to claim 1, characterized in that: In the second method, the CO2 blowing pressure is 0.05MPa~0.5MPa, and the blowing time is 5s~90s; and / or, the compressed air blowing pressure is 0.05MPa~0.5MPa, and the blowing time is 5s~40s; and / or, the inorganic binder sand is immersed in an organic curing agent for secondary hardening, and the immersion time is 0.5s~600s.

5. The process according to claim 1, characterized in that: In the third method, the time for immersing the formed inorganic binder sand into the organic curing agent is 0.5s to 600s.

6. The process according to claim 1, characterized in that: In the fourth method, an organic curing agent is sprayed on the surface of the formed inorganic binder sand to harden it, and the number of spraying times for hardening is 1 to 10 times.

7. The process according to any one of claims 1 to 6, characterized in that: The raw materials of the inorganic binder sand include: raw sand, binder, and hardening accelerator; wherein the binder is added in an amount of 2% to 3% of the mass of the raw sand, and the hardening accelerator is added in an amount of 0 to 50% of the mass of the binder; preferably, the binder is water glass or modified water glass.

8. The process according to claim 1, characterized in that: The process of forming inorganic binder sand by 3D printing the raw sand, binder and organic curing agent layer by layer and hardening the inorganic binder sand at the same time is one of the following methods: Method 1), laying raw sand on the 3D printing instrument, then spraying the binder and organic curing agent on the surface of the raw sand in sequence, and 3D scanning and forming; repeating the above process until the 3D printing is completed; Method 2), mix the raw sand and the binder, then spread the mixture on the 3D printing instrument, spray the organic curing agent, and 3D scan and shape; repeat the above process until the 3D printing is completed; Preferably, the mass ratio of raw sand, binder and organic curing agent is controlled at 100:2-3:0.1-1.0; Preferably, the binder is water glass or modified water glass, and the added amount is 2% to 3% of the mass of the original sand.

9. The process according to claim 8, characterized in that: A hardening accelerator is added to the raw sand, and the amount of the hardening accelerator added is 1 to 50% of the mass of the binder; preferably, the hardening accelerator is at least one of bauxite, crystalline silica, amorphous silica, fumed silica, silicon powder, microsilica powder, wollastonite powder, and surface-modified silica.

10. A method for surface repair and / or surface hardening of sand with an inorganic binder, characterized in that: The method of claim 1 is to use method 4 in the process method to carry out inorganic binder sand surface repair and / or surface hardening.

Citation Information

Patent Citations

  • Latently curable binder compositions which contain cure enhancing agents

    CA1330604C

  • Novel liquid curing agent used for 3D sand mold printing inorganic binder and preparation method of novel liquid curing agent

    CN105057566A

  • Additional forming material for three-dimensional printing

    CN106825387A

  • Method for improving fluidity of water glass for casting through polyethylene glycol

    CN110052572A

  • Casting sand mold based on three-dimensional jet printing and forming method thereof

    CN110918883A